2010
DOI: 10.1007/s10552-010-9562-1
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to the sun and risk of skin and lip cancer among male wage earners in Denmark: a population-based case–control study

Abstract: The results support the hypothesis of a decreased risk of non-melanoma skin cancer and an increased risk of lip cancer among outdoor workers in the Northern Hemisphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 33 publications
0
38
0
5
Order By: Relevance
“…To assess the validity of our JEM, we applied the JEM for outdoor work to data from a corresponding study of lip cancer, carried out by Kenborg et al 16 Solar ultraviolet radiation has long been considered to cause lip cancer, and several studies have shown a positive association between outdoor occupations and lip cancer 17–19. Thus, if our JEM for outdoor work functioned properly, we expected to observe a rising gradient of lip cancer with increasing outdoor work.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the validity of our JEM, we applied the JEM for outdoor work to data from a corresponding study of lip cancer, carried out by Kenborg et al 16 Solar ultraviolet radiation has long been considered to cause lip cancer, and several studies have shown a positive association between outdoor occupations and lip cancer 17–19. Thus, if our JEM for outdoor work functioned properly, we expected to observe a rising gradient of lip cancer with increasing outdoor work.…”
Section: Methodsmentioning
confidence: 99%
“…High occupational UVR exposure is assumed to be associated with skin cancer (Bauer et al 2011;Downs et al, 2009;Hakansson et al, 2001;Kenborg et al, 2010;Lichte et al, 2010;Radespiel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Deux études s'intéressaient uniquement au cancer des lèvres [12,33], les autres aux CCB et/ou aux cancers des voies aéro-digestives supérieures.…”
Section: Résultatsunclassified
“…Des facteurs environnementaux peuvent être associés aux CCB, notamment le travail à l'extérieur pour les cancers des lèvres, liés à l'exposition aux UV [12], mais également l'exposition aux pesticides et à certains solvants [17]. Les traitements immunosuppresseurs prescrits dans les greffes d'organe seraient associés à un risque plus important de cancer des lèvres par le renforcement de l'action des UV [33].…”
Section: Résultatsunclassified